n = 0 ∑ ∞ ( n + 2 ) n ! 3 n = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Why don't write a short Computer Program ? Let your computer do the job for you!
Here's the C Program :
int main()
{
long int g,d=1;
printf("The number of Test : ");
scanf("%ld",&g);
while(g--){
printf("The Precision (500 for highest Precision) :");
double s=.5,n=1,x;
scanf("%lf",&x);
while(x--){
double f=1,i=1;
while(i<=n){f*=i;i++;}
s+=pow(3,n)/(f*(n+2));
n++;
}
printf("%.14lf",s);
d++;
printf("\n\n");
}
return 0;
}
You might wanna Download the code on Pastebin.
There are thousands of ways of solving a problem!
Problem Loading...
Note Loading...
Set Loading...
Firstly I'll try to create a factorial on the bottom and rearrange to produce a sum including the series of the form n = 0 ∑ ∞ n ! x n = e x . n = 0 ∑ ∞ ( n + 2 ) n ! 3 n = n = 0 ∑ ∞ ( n + 2 ) ! 3 n ( n + 1 ) = n = 0 ∑ ∞ ( n + 2 ) ! 3 n ( n + 2 − 1 ) = n = 0 ∑ ∞ ( n + 1 ) ! 3 n − n = 0 ∑ ∞ ( n + 2 ) ! 3 n = 3 1 n = 1 ∑ ∞ n ! 3 n − 9 1 n = 2 ∑ ∞ n ! 3 n = 3 1 ( n = 0 ∑ ∞ n ! 3 n − 1 ) − 9 1 ( n = 0 ∑ ∞ n ! 3 n − 4 ) = 9 2 n = 0 ∑ ∞ n ! 3 n + 9 1 = 9 1 ( 2 e 3 + 1 )